A CRITICAL ANALYSIS OF MOTIVATIONAL FACTORS AFFECTING JOB HOPPING BEHAVIOUR OF PROFESSIONALS - Manjot, Dr. Shashi Kala (Chelonian Research Foundation, 2023)
Banking is a sector which is uncertain to a great extent. Here, people are more probably for money rather than changing the world. Although every employer wants consistency, commitment and stability of employees but that one company man does not exist now days. Our ancestors might have worked for one organization for ages but same is not the case with millennial employees. Long ago, recruiters used to frown upon seeing many jobs on one resume but the scenario has totally changed. When it comes to job hopping, it should be constructive, that is, one must go on with planning to achieve goals. Motivation is one of the greatest factors that play a role in job hopping of employees. Both intrinsic and extrinsic factors play a significant role in retention or turnover of employees. The purpose of this conceptual paper is to review the existent literature on effect of intrinsic and extrinsic motivational factors on job hopping. Keywords: Intrinsic motivational factors, extrinsic motivational factors, Turnover intention, Job hopping.